Multifunctional metabolites of Streptomyces kunmingensis BS19 from bamboo rhizosphere soil - Sangeetha, Murthy; Sasirekha, Sivakumar; Mahendran, Jaganathan; Sivarajan, Anbalmani; Radhakrishnan, Manikkam; Manigundan, Kaari; Dastager, Syed G.; Sengottuvelu, Singaravel; Balagurunathan, Ramasamy (International Microbiology, 2024)
A pigmented bioactive molecule from Streptomyces kunmingensis BS19 was isolated, characterized, and evaluated for anti-infective, antiproliferative, and wound-healing properties. The yellow–red pigment produced from the strain BS19 showed promising activity against methicillin-resistant Staphylococcus aureus (MRSA) and Mycobacterium tuberculosis. Extracellular bioactive pigment from the strain BS19 was produced by agar surface fermentation and purified through bioassay guided preparative HPLC-based purification. Based on the results of UV, FT-IR, GC–MS, 1H NMR, and 13C NMR spectral analyses, the purified pigment was identified as a chromopeptide class of molecule with phenoxazinone chromophore. Its molecular weight was determined as the chemical formula C64H90N12O16 and molecular weight 1283 g/mol. It exhibited promising antimicrobial activity against Staphylococcus aureus (ATCC 1720) and antiproliferative activity against 14 types of human cancer cell lines. It showed good in vivo wound-healing activity in the rat model. The present study explored Streptomyces kunmingensis as a newly added source for the isolation of chromopeptide antibiotics for antimicrobial, wound-healing, and anticancer applications.